Cuidados de enfermería a la mujer con aborto por automedicación - Págalos Basantes, Katherine Lizbeth (2022)
ABSTRACT: Induced abortion results from maneuvers performed to interrupt pregnancy, leading to complications that put the woman's life at risk, thus increasing morbidity and mortality; therefore, the nursing care provided to postabortion women is of great importance. A documentary and crosssectional study were carried out to determine nursing care for women with self-medication abortion by collecting information from several documents published on scientific bases: Scielo, Dialnet, Elsevier, Medline, Ipas, Google Scholar, and official pages such as the World Health Organization; issued between 2017 - 2022, of which 70 bibliographical references were taken; For the results of the investigation, first the scientific articles that met the inclusion criteria were analyzed and selected, then the concepts of abortion, self-medication and care were reviewed; and the NIC interventions were determined. The main complications in induced abortion are hemorrhages, sepsis, pain, infertility, psychological guilt, depression, and sadness; the most consistent care: control bleeding pain, administer analgesic medication, monitor vital signs and provide emotional support; in those specific ones such as to monitor the color and amount of bleeding, record the level of hemoglobin and hematocrit, observe the signs and symptoms of infection and advise on the use of contraceptives. Firmado electrónicamente por: SOFIA FERNANDA FREIRE CARRILLO Reviewed by: Lic. Sofía Freire Carrillo ENGLISH PROFESSOR C.C. 0604257881